It's been a hard day's night: The concentration and intensification of work in late 20th century Britain - Francis Green (University of Kent, Department of Economics, 1999)
I investigate evidence concerning two indicators of the pressure of work, namely work hours and the intensity of effort during work hours ("work effort"). Interest in both is motivated by efficiency and welfare considerations, but analysis is typically attenuated by poor measurement. I first show how it is possible to derive measures of changing work effort from survey responses. Then, for Britain, I examine the trend in the distribution of work hours since 1977, and present evidence on changing work effort and correlates thereof. My main findings are: (a) Average hours of work per worker levelled off at the start of the 1980s, following a long historic fall, but have not increased since. However, since 1981 the dispersion of hours has increased, and working hours have been concentrated into fewer households. (b) Work effort was intensified, especially in manufacturing, during the 1980s. (c) Across Britain from 1992 to 1997, there was an increase in "discretionary effort" and an even greater rise in "constrained effort", with the increases being somewhat faster for women than for men. (d) Between 1986 and 1997 there have been substantial increases in the number of factors inducing hard work from employees. The most notable proximate source of increased pressure for hard work has come from colleagues. (e) Both at the industry level, and at the establishment level, rises in effort have been associated with rises in productivity. (f) Increases in effort are associated with self-reported increases in stress.
Keywords: J22; 330; Labour Supply